Respectability and reputation: Tracing intersections of race, class and gender in news discourses of violence against women - van Niekerk, Taryn (PINS-Psychology in Society, 2018)
This paper investigates how gendered inequalities are reproduced in printed news media discourses of men’s violence against women and how they intersect with the racial and classed dimensions of survivor and perpetrator identities in two Cape Town newspapers. A total of 113 reports on violence against women were collected from two newspapers that drew the largest readership in the Western Cape Province between 2011 and 2013. A thematic decomposition analysis revealed the presence of a discourse of respectability, which shed light on how pathologising representations “other” and blame victims who are thought to stray from respectability, particularly poor black women who find themselves on the periphery of this discourse of femininity. In contrast, perpetrators of violence against women were represented through the lens of race and class, and predominantly through reputable performances of masculinity, silencing their accountability. Understanding violence as an intersectional experience – defined by race, class, sexuality and gender in the context of post-apartheid South Africa – is central to the analysis. A critical comparison between the two newspapers’ reporting styles is offered. Furthermore, the news media’s tendency to reproduce racial and gendered stereotypes of victims and perpetrators of violence and to marginalise some voices over others is problematised.